Enhancing Photocatalytic Activity of Bismuth Ferrite (BiFeO3) via Gadolinium and Copper Doping: A Sol-Gel Synthesis and Characterization Study - Beerelli Rajitha; Padma Suvarna (Journal of Multidisciplinary Applied Natural Science, 2024)
In this current research work, the sol-gel method was employed to synthesise, characterize and evaluate the photocatalytic activity of bismuth ferrite (BiFeO3, BFO) doped with two distinctive components consisting of a rare earth element Gadolinium (Gd) and a transition metal Copper (Cu). The dopant concentrations were systematically varied with different weight percentages (wt.%) denoted as Bi1-xGdxFe1-yCuyO3 (where ‘x’ = 0.10, 0.15 and 0.20 wt.%, where ‘y’ = 0.05, 0.10, and 0.15 wt.%). Subsequently, characterizations of the prepared samples were conducted using an array of cutting-edge analytical techniques including X-ray diffraction (XRD), filed emission scanning electron microscopy (FE-SEM), energy dispersive X-ray analysis (EDAX), and transmission electron microscopy (TEM). The XRD analysis results indicated that the presence of small impurity peaks was found in both Gd-doped BFO and GdCu-doped BFO. The FE-SEM and TEM results provided confirmation that the material was observed as a spherical shape, and the elemental compositions were also confirmed through EDAX analysis. The photocatalytic degradation of Rhodamine B dye under the influence of visible light irradiation was carried out and the results revealed varying degradation times, specifically, for Gd and Cu-doped BFO (Gd and Cu = 0.1 wt.%) achieved almost 98% degradation occurred in 30 minutes.